TINJAUAN PENERAPAN UUK-PKPU TERHADAP HAK KREDITOR PEMEGANG HAK TANGGUNGAN DALAM MELAKSANAKAN EKSEKUSI AGUNAN - Sihotang, Biner; Naiborhu, Mesa Indra (Collegium Studiosum Journal, 2025)
The Bankruptcy and Postponement of Debt Payment Obligations Law (UUK-PKPU) provides space for debtors to postpone debt payments and restructure their obligations. However, the existence of a 90-day stay provision in the PKPU process has caused serious problems with the rights of creditors holding mortgage rights, especially in efforts to carry out collateral execution. This study aims to analyze the application of the provision in the context of legal protection of creditors, review its compatibility with the principles of legal certainty and justice, and criticize the potential for legal smuggling that may occur in practice. Through a normative approach and literature study, including linking the conflict of norms between UUK-PKPU and the Mortgage Rights Law (UUHT), this article shows that the dominance of the lex posterior derogat legi priori principle in this context often ignores substantive justice for creditors. The results of this study emphasize the need for legal reform of the PKPU stay period and the balancing of protection between debtors and creditors in the process of postponing debt payment obligations. These findings reinforce the urgency of regulatory reorganization to prevent irregularities in the implementation of bankruptcy law in Indonesia.